Theoretical and Practical Outlines for Writing Abstract in English - Benčič, S. (Ye.A.Buketov Karaganda State University Publ., 2014)
Recent academic and professional writing regularly requires from authors to write competent abstracts. The paper deals with theoretical norms and practical outlines about mentioned writing skill. Many text books and studies have been already devoted to that topic, so author of the paper compiled basic hints which are understandable and useable in English for academic purposes teaching or in practice. Besides theoretical background and definitions, practical patterns are the main asset of the paper. The paper will help students and university teachers who are concerned in writing in English and to meet the demands they will face in college, university, as well as on the job.
Ағылшын тілінде түйін жазудың теориялық жəне практикалық сипаттамалары
Теоретическая и практическая характеристики составления аннотации на английском языке
Keywords: academic writing; descriptive and informative abstracts; puzzle scheme; norms; outlines; usage; tracts puzzle scheme; theoretical background; practical hints